Japanglish: The Benefits of English Proficiency for Japanese Language Students' Vocabulary Acquisition in North Sumatra - Gapur, Abdul; Taulia (International Journal of Culture and Art Studies, 2023)
Japanglish is a popular term for absorbing English words into the Japanese language. The phenomenon emerged due to the global usage of English as an international language, which has influenced other languages, including Japanese. As a result, many English loanwords have been absorbed into the Japanese language, particularly for modern terminology. These loanwords are known as gairaigo (å¤–æ¥èªž) or katakanago (ã‚«ã‚¿ã‚«ãƒŠèªž). Although the incorporation process involves morphological and phonological changes, English loanwords are easily recognizable to those who understand English. This study aims to prove that English Proficiency among Japanese language learners can help improve their mastery of Japanese vocabulary and conversational ability. The study was conducted by providing special instructions on the formation and usage of Japanese loanwords in conversation. The study approach is qualitative with a descriptive method, employing behavioral theory and pre-test and post-test evaluation methods. Data were collected through observation of the teaching process and pre-test and post-test results from Japanese language students in Sumatra Utara. The findings indicate that English language proficiency among students offers advantages and influence in the mastery of Japanese vocabulary, especially in loanwords, and facilitates communication in conversation.